Process survey and effects of low temperature storage on patil - Seguia, Cyrene Pauya (2011.)
This study conducted a process survey of the processing of Patil in Tacurong Sultan Kudarat.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Patil